Analisis Kemampuan Pemecehan Masalah Matematis Ditinjau Dari Gender Siswa Kelas VII Mts Manba’ul ‘Ulum Dasan Ketujur - Zuriatullaila, Zuriatullaila; Evendi, Erpin (Mathematic Education Departement, State Islamic University of Mataram, 2023)
This research aims to describe mathematical problem solving abilities in terms of students' gender. This research uses a qualitative approach, a type of descriptive qualitative research. This research was carried out at MTs Manba'ul 'Ulum Dasan Ketujur. The subjects in this research were 6 students out of 40 students in class VII, 3 male subjects and 3 female subjects. The instruments used were a mathematical problem solving ability test and an interview guide. The results of the research are students' mathematical problem solving using polya steps and problem solving levels according to the Vermont Department of Education in terms of gender are: (1) male subjects in the high category meet 3 indicators; (2) female subjects in the high category meet 4 indicators; (3) male subjects in the medium category meet 2 indicators; (4) female subjects in the medium category meet 3 indicators; (5) male subjects in the low category fulfill 1 indicator; (6) female subjects in the low category fulfill 2 indicators.